The Value of Social Care Character Education through Zikir Tarekat Qadiriyah Wa Naqsyabandiyah - Suteja; M. Sugeng Sholehuddin; Irfan Hania (Faculty of Education and Teacher Training, Institut Agama Islam Negeri Pekalongan, 2022)
The purpose of this research is to make a systematic, factual and accurate description, description or description of the facts, characteristics and relationships between the phenomena being investigated. Data collection techniques used in this study include observation, in-depth interviews, and documentation studies. The data analysis used in this research is qualitative data analysis. This analysis is done by working with data, organizing data, sorting it into manageable units, synthesizing it, looking for and finding patterns, discovering what is important and what is learned, and deciding what to tell others. The results of this study indicate that the social care character education formed by the Qodiriyah wan Naqsabandiyah Order is to use two methods, namely dhikr and tazkiyat al-Nafs. The process of developing the personality of Tarekat Qodiriyah wa Naqsabandiyah Bongas Indramayu students, as is usually the case in the orderekat world, is carried out by the method of dhikr and soul cleansing (tazkiyat al-Nafs). Their motive for entering the tarekat is almost entirely based on economic motives. The guidance carried out has not succeeded in creating an inclusive student personality and has social concern in interacting with the community. Keywords: Dzikir, Social Care, Qodiriyah wan Naqsyabandîyah.